Cortical Auditory Event-Related Potentials and Categorical Perception of Voice Onset Time in Children With an Auditory Neuropathy Spectrum Disorder - McFayden, Tyler C.; Baskin, Paola; Stephens, Joseph D. W.; He, Shuman (Frontiers in Human Neuroscience, 2020)
Objective: This study evaluated cortical encoding of voice onset time (VOT) in quiet and noise, and their potential associations with behavioral categorical perception of VOT in children with auditory neuropathy spectrum disorder (ANSD). Design: Subjects were 11 children with ANSD ranging in age between 6.4 and 16.2 years. The stimulus was an /aba/-/apa/ vowel-consonant-vowel continuum comprising eight tokens with VOTs ranging from 0 ms (voiced endpoint) to 88 ms (voiceless endpoint). For speech in noise, speech tokens were mixed with the speech-shaped noise from the Hearing In Noise Test at a signal-to-noise ratio (SNR) of +5 dB. Speech-evoked auditory event-related potentials (ERPs) and behavioral categorization perception of VOT were measured in quiet in all subjects, and at a SNR of +5 dB in seven subjects. The stimuli were presented at 35 dB SL (re: pure tone average) or at 115 dB SPL if this limit was less than 35 dB SL. In addition to the onset response, the auditory change complex (ACC) elicited by VOT was recorded in eight subjects. Results: Speech evoked ERPs recorded in all subjects consisted of a vertex positive peak (i.e. P1), followed by a trough occurring approximately 100 ms later (i.e. N2). For results measured in quiet, there was no significant difference in categorical boundaries estimated using ERP measures and behavioral procedures. Categorical boundaries estimated in quiet using both ERP and behavioral measures closely correlated with the most-recently measured Phonetically Balanced Kindergarten scores. Adding a competing background noise did not affect categorical boundaries estimated using either behavioral or ERP procedures in three subjects. For the other four subjects, categorical boundaries estimated in noise using behavioral measures were prolonged. However, adding background noise only increased categorical boundaries measured using ERPs in three out of these four subjects. Conclusions: VCV continuum can be used to evaluate behavioral identification and neural encoding of VOT in children with ANSD. In quiet, categorical boundaries of VOT estimated using behavioral measures and ERP recordings are closely associated with speech recognition performance in children with ANSD. Underlying mechanisms for excessive speech perception deficits in noise may vary for individual patients with ANSD.